2020
DOI: 10.1093/nsr/nwaa041
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic T-cells and inflammatory monocytes incite inflammatory storms in severe COVID-19 patients

Abstract: Pathogenic human coronavirus infections, such as severe acute respiratory syndrome CoV (SARS-CoV) and Middle East respiratory syndrome CoV (MERS-CoV), cause high morbidity and mortality 1,2 . Recently, a severe pneumonia-associated respiratory syndrome caused by a new coronavirus was reported at December 2019 (2019-nCoV) in the city Wuhan, Hubei province, China [3][4][5] , which was also named as pneumonia-associated respiratory syndrome (PARS) 6 . Up to 9th of February 2020, at least 37, 251 cases have been r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
1,134
8
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,037 publications
(1,237 citation statements)
references
References 34 publications
38
1,134
8
24
Order By: Relevance
“…Although the pathogenesis of severe COVID-19 remains incompletely understood, emerging data suggests that organ dysfunction and poor outcomes may be mediated by high levels of pro-inflammatory cytokines including IL-6 and dysregulated coagulation and thrombosis. 13,14,19 Continued investigation of these pathological processes and the utility of their biomarkers is needed given recent reports of corticosteroid use and ongoing clinical trials of IL-6-receptor antagonists among COVID-19 inpatients, as well as rapidly evolving guidelines for anti-coagulation in this population. 17,20,21 Consistent with unadjusted data from China, 3 and Italy, 8 hypertension was independently associated with poor in-hospital survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of severe COVID-19 remains incompletely understood, emerging data suggests that organ dysfunction and poor outcomes may be mediated by high levels of pro-inflammatory cytokines including IL-6 and dysregulated coagulation and thrombosis. 13,14,19 Continued investigation of these pathological processes and the utility of their biomarkers is needed given recent reports of corticosteroid use and ongoing clinical trials of IL-6-receptor antagonists among COVID-19 inpatients, as well as rapidly evolving guidelines for anti-coagulation in this population. 17,20,21 Consistent with unadjusted data from China, 3 and Italy, 8 hypertension was independently associated with poor in-hospital survival.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Zhou and colleagues recently reported on the presence of a significantly higher percentage of CD14 + CD16 + inflammatory monocytes in the peripheral blood of COVID-19 patients compared to normal healthy controls. 17,18 They also reported that the percentage of CD14 + CD16 + monocytes was much higher in severe pulmonary syndrome patients from ICU. They also showed that these monocytes had the capability of secreting GM-CSF and similar to our findings could also secrete IL-6, which was higher in ICU patients, in association with cytokine storm.…”
Section: In a Review Of The Causes And Consequences Of Cytokine Stormmentioning
confidence: 94%
“…Very interestingly, high levels of CD4 + cells expressing both GM-CSF and IL-6 were found in COVID-19 patients, along with GM-CSF-secreting CD14 + CD16 + , compared to healthy controls. Even more intriguingly, Th1 cells expressing both GM-CSF and IFN-γ were detected exclusively in ICU patients, thus suggesting a potential contribution of GM-CSF to CRS [300]. These data are further supported by the evidence that human pulmonary microvascular endothelial cells (HPMEC) are able to secrete GM-CSF following an inflammatory stimulus such as LPS, suggesting a potential important role in the pathogenesis of ARDS, in which increased levels of GM-CSF are present in BAL fluid [301].…”
Section: Granulocyte-monocyte Colony Stimulating Factormentioning
confidence: 97%